The Positive Effect of an Online Appointment Portal on a Breast Cancer Screening Program - Chiereghin, Angela; Pizzi, Lorenzo; Squillace, Lorena; Bazzani, Carmen; Roti, Lorenzo; Mezzetti, Francesca (Applied Clinical Informatics, 2023)
Background The adoption of web-based appointment methods by health care systems is increasing.Objectives This study primarily aimed to evaluate in the setting of an organized breast cancer screening program the actual usage of an online appointment portal by the target population, i.e., how the online tool was used (type and timing of the actions performed) and by whom (users' characteristics); the effect of coronavirus disease 2019 (COVID-19) on its usage was also investigated. The effect of adopting this tool on the attendance to breast cancer screening was contextually investigated.Methods Electronic data records of 75,903 women (45–74 years old, residing in the territory of Bologna Local Health Authority) were retrospectively reviewed.Results In total, 12.4% of women logged into the online portal at least once. Most of them (79.9%) rescheduled, 15.7% viewed, and 4.4% cancelled their own appointment. In addition, 40.6% of all rescheduling actions were performed by the online portal; the remaining was performed by the toll-free number/dedicated email address. The highest peak (13.8%) of web accesses was registered at 10 a.m. Monday to Friday, when the toll-free number service is available. Percentages of portal usage were higher: (1) among the younger women, of Italian nationality, and for the first time invited to mammographic screening (p < 0.0001), and (2) in the pandemic period versus the prepandemic period (12.5 vs. 8.6%, respectively; p < 0.001). Finally, when compared to not using, the online portal usage led to an overall reduction in the no-show rate of almost 20% (p < 0.0001).Conclusion The action mainly performed by using the online appointment portal was the appointment rescheduling. The usage of this tool had a positive effect on the no-show rate and it can be speculated that has led to a reduction of the request load to be handled by the center's screening staff. Finally, this study confirmed that the COVID-19 pandemic boosted the use of digital technologies.
Keywords: organized breast cancer screening; online appointment portal; appointment scheduling; no-show rate; COVID−19 pandemic